How energy audits promote SMEs' energy efficiency investment - Fotios Kalantzis; Debora Revoltella (European Investment Bank (EIB), 2019)
This paper assesses the role of energy audits in promoting energy-efficiency measures in SMEs. It benefits from the data collected within the European Investment Bank Surveys in 2017 and 2018, involving information about energy audits and energy-efficiency investments of some 12,500 signatures from EU28 Member States per year. Our findings suggest that energy audit is a useful tool in overcoming the information barriers and facilitating investments in energy-efficiency measures. In fact, their information is more crucial for small firms and for investments in support processes such as lighting, wall insulation etc. than in production processes such as replacement of machinery and equipment. However, we found that the beneficial impact of energy audits cease to exist when firms are finance constrained. Finally, our results indicate that information campaigns are one of the most efficient available instruments among other instruments (regulatory, financial and voluntary agreements) for promoting energy audits in SMEs.
Keywords: P28; Q41; Q48; 330; energy audit; propensity score matching; energy efficiency; European Investment Bank survey